Ethylene insertion in the presence of new alkoxysilane electron donors for Ziegler-Natta catalyzed polyethylene - Sutiam Kruawan (2018)
© 2017 Density functional theory (DFT) calculations have been carried out to investigate the ethylene insertion pathway using a Ziegler-Natta catalyst in the absence and presence of electron donor (ED) systems on the (1 1 0) MgCl 2 surface. The coadsorptions of four different EDs i.e. Si(OEt) m Cl n (m + n = 4) were investigated. The presence of Si(OEt) 4 on the (1 1 0) MgCl 2 surface with the preferential bidentate mode was found to have the strongest adsorption energy (ΔE ads ). The potential energy surface (PES) map indicated that the reaction mechanism of the ethylene insertion into the Ti[sbnd]C bond on the (1 1 0) Mg 13 Cl 26 .TiCl 3 -CH 2 CH 3 surface is pseudo-concerted. As the differences in the intrinsic activation energies (ΔE a ) obtained from all systems are so small, this energy cannot be used to fully explain the significant changes in the rates of the ethylene insertion reaction observed when an ED is employed. Here, the apparent activation energy (ΔΔE aa ) was calculated using the PBE functional and the 6-31G(d, p) basis set for C, H, O, Mg and Cl, and the LANL2DZ basis set with an ECP function for the Ti atom. All EDs presented in this work in the ethylene insertion reaction can significantly reduce the apparent energy barrier when compared to an absence of any ED system. The obtained ΔΔE aa for the four ED complexes were found to decrease in the following order: SiOEtCl 3   >  Si(OEt) 2 Cl 2   >  Si(OEt) 3 Cl  >  Si(OEt) 4 . The obtained data lead to the conclusion that Si(OEt) 4 is the most suitable ED to increase the productivity of PE in the presence of alkoxysilane.